HYVET Study results: importance for clinical practice - S. V. Nedogoda (Кардиоваскулярная терапия и профилактика)
HYVET Study was aimed at assessing the effects of indapamide SR (1,5 mg/d), as monotherapy or combined with an ACE inhibitor perindopril (2-4 mg/d), compared to placebo, on the risk of stroke and other cardiovascular events in arterial hypertension patients aged over 80 years. Active indapamide SR therapy significantly reduced the risk of fatal and non-fatal stroke by 30%, fatal and non-fatal heart failure – by 64%, fatal stroke – by 39%, allcause mortality – by 21%, with additional reduction in the risk of cardiovascular and non-cardiovascular mortality, coronary heart disease and chronic heart failure mortality.